Assessing Biodiversity Change of Butterfly Species (Macro-lepidoptera) in Four Bioregions in Finland - Rahman, Sumaiya (2024)
Loss of biodiversity as a result of changes in land use and climate is a major hazard to ecosystems worldwide, including Finland. Effective conservation requires monitoring and measuring changes in biodiversity over time, but this was difficult owing to poor and restricted data availability. While national-level evaluations like the Red List is helpful to comprehend broad patterns in biodiversity loss and change, they may be unable to fully capture changes of the whole species community (all species) and regional differences. The purpose of this research was to assess and quantify butterfly (Macro-lepidoptera) biodiversity changes in Finland at the regional levels. The research made use of butterfly-specific biodiversity data culled from the Laji.fi database. Biodiversity indicators were calculated using the available data, and the rate and significatively of changes in biodiversity were evaluated using statistical analysis tool such as “R”. The primary objectives of this study were to compare biodiversity trends recorded in different regions and evaluated the temporal changes in butterfly biodiversity. For efficient conservation planning and resource allocation, knowledge of biodiversity patterns across space and time is essential. The results of this thesis may inform conservationists and policymakers on how butterfly species in Finland are adjusting to changing environmental conditions.